Enhanced mechanical properties of PLA/PLAE blends via well-dispersed and compatilized nanostructures in the matrix. Issue 30 (8th March 2016) - Cai, Shenyang; Zeng, Chao; Zhang, Naiwen; Li, Jianbo; Meyer, Markus; Fink, Rainer H.; Shi, Donglu; Ren, Jie
Abstract : The mechanical properties of PLA are significantly enhanced by the well-dispersed and compatilized nanostructures in the matrix of PLA/PLAE blends. Abstract : Polylactide (PLA) was toughened by a PLA-based thermoplastic elastomer (PLAE). PLAE was prepared by chain extension of PLA copolymer derived from polylactic acid (PLA) and poly(tetramethylene ether glycol) (PTMEG) via melt polycondensation. The tensile strength of the toughened-PLA (PLAE30) reached 70 MPa, while the elongation at break was found to be above 140% compared to its plain PLA counterpart. The relationship between the phase morphology of the blends and their mechanical behavior was investigated with atomic force microscopy (AFM), scanning electron microscopy (SEM), and scanning transmission X-ray microscopy (STXM). It was found that the well-dispersed nanoscale structures in the matrix of PLA/PLAE blends are mainly responsible for the significantly enhanced mechanical properties. Also discussed are the detailed microstructural development in PLAE and the toughening mechanism.